Penerapan Model Pembelajaran Kooperatif Di SD Negeri Pondok Jagung Timur Tangerang Selatan - Magdalena, Ina; Ningrum, Dwi Rahayu Kusuma; Aulya, Zahra (Lembaga Yasin AlSys, 2023)
The goal is to make learning at Pondok Jagung Timur Elementary School better and motivate students to take lessons seriously. These teachers must be equipped with good teaching methods, so that they are creative in using various cooperative learning models. This program aims to build an understanding of the ability to choose learning models that are appropriate to learning conditions. Because ideal learning is learning that always changes according to ongoing conditions. The final result obtained from this program is an increase in teacher creativity at Pondok Jagung Timur Elementary School in the teaching and learning process. Especially in the use and application of innovative learning models, such as cooperative learning models. The aim is to attract students’ interest so that they always participate in learning in pleasant conditions. So the results will improve the quality of the implementation of the learning process and improve teacher performance in teaching.